2022
DOI: 10.1002/cbf.3763
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and mitochondrial dysfunction insights into the impact of the progression of non‐alcoholic fatty liver disease

Abstract: A metabolic problem occurs when regular functions of the body are disrupted due to an undesirable imbalance. Nonalcoholic fatty liver disease (NAFLD) is considered as one of the most common in this category. NAFLD is subclassified and progresses from lipid accumulation to cirrhosis before advancing to hepatocellular cancer. In spite of being a critical concern, the standard treatment is inadequate. Metformin, silymarin, and other nonspecific medications are used in the management of NAFLD.Aside from this avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 138 publications
0
7
0
1
Order By: Relevance
“… 60 However, there is evidence suggesting that changes in the epigenetic landscape contribute to mitochondrial dysfunction. 71 Altered methylation near the mt-Nd6 gene has previously been observed in diabetes or hepatic steatosis where expression negatively correlated to severity. 67 , 72 , 73 Similar to our findings, this hypermethylation was associated with the altered transcription of the corresponding gene in liver biopsies of patients with NASH, emphasizing the regulatory importance of MT-ND6, a subunit of complex I of the mitochondrial respiratory chain.…”
Section: Discussionmentioning
confidence: 92%
“… 60 However, there is evidence suggesting that changes in the epigenetic landscape contribute to mitochondrial dysfunction. 71 Altered methylation near the mt-Nd6 gene has previously been observed in diabetes or hepatic steatosis where expression negatively correlated to severity. 67 , 72 , 73 Similar to our findings, this hypermethylation was associated with the altered transcription of the corresponding gene in liver biopsies of patients with NASH, emphasizing the regulatory importance of MT-ND6, a subunit of complex I of the mitochondrial respiratory chain.…”
Section: Discussionmentioning
confidence: 92%
“…At the genetic level, alterations in gene expression play a pivotal role in initiating and advancing the disease. This modulation is largely driven by epigenetic mechanisms, including DNA methylation, histone modifications, and non-coding RNAs, which impact the expression of genes without altering the DNA sequence itself [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle factors such as weight gain and lack of physical activity have been shown to impact the pathogenesis of NAFLD through epigenetic mechanisms [ 4 ]. Epigenetic changes intricately participate in modulating multiple processes such as lipid metabolism, insulin sensitivity, mitochondrial function, and redox balance, all of which are relevant to the pathophysiology of NAFLD [ 4 , 5 ]. Because epigenetic modifications are reversible, they offer a flexible interface between an individual and their environment, making them attractive targets for therapeutic interventions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetics is the study of changes in gene expression and phenotypic variations that are not the result of changes in DNA sequences [113]. Methylation of DNA and modification of histones are among the most studied epigenetic modifications [114]. DNA methylation is a significant epigenetic modification of cytosine bases in cytosine‐phospho‐guanine (CpG) dinucleotides, called CpG islands [115].…”
Section: Omics Technologies (Except Radiomics) For Diffuse Liver Dise...mentioning
confidence: 99%
“…There is a link between the methylation status of CpG islands and gene suppression, especially when methylation is in the regulatory and promoter regions of genes [115]. Some genes of patients with NAFLD were found to have different methylation levels than the same genes of healthy individuals [114], and a next‐generation sequencing analysis of liver samples showed that patients with NAFLD had significantly lower levels of global DNA methylation than those with healthy controls [115]. In addition, changes in DNA methylation levels were found to be associated with NAFLD progression from mild to advanced and may be highly predictive of fibrosis [116].…”
Section: Omics Technologies (Except Radiomics) For Diffuse Liver Dise...mentioning
confidence: 99%